Handling Sign Language Data: The Impact of Modality - Quer, Josep; Steinbach, Markus (Frontiers in Psychology, 2019)
Natural languages come in two different modalities. The impact of modality on the grammatical structure and linguistic theory has been discussed at great length in the last 20 years. By contrast, the impact of modality on linguistic data elicitation and collection, corpus studies and experimental (psycholinguistic) studies is still underinvestigated (van Herreweghe/Vermeerbergen 2012; Orfanidou et al. 2015). In this paper, we address specific challenges that arise in judgement data elicitation and experimental studies of sign languages. These challenges are related to the socio-linguistic status of the Deaf community and the larger variability across signers within the same community, to the social status of sign languages, to properties of ;he visual-gestural modality and its interface with gesture, to methodological aspects of handling sign language data, and to specific linguistic features of sign languages. While some of these challenges also pertain to (some varieties of) spoken languages, other challenges are more modality-specific. In addition, the special combination of the challenges discussed in this paper seems to be a specific facet empirical research on sign languages is faced with. In addition, we discuss the complementarity of theoretical approaches and experimental studies and show how the interaction of both approaches contributes to a better understanding of sign languages in particular and linguistic structures in general.